2020
DOI: 10.5005/jp-journals-10005-1782
|View full text |Cite
|
Sign up to set email alerts
|

Dentistry during and after COVID-19 Pandemic: Pediatric Considerations

Abstract: A bstract This article is a rumination on the outbreak of the dreaded coronavirus disease-2019 (COVID-19) pandemic which has engulfed both the developed and the developing countries, thereby causing widespread global public health concerns and threats to human lives. Although countries have made varied efforts, the pestilence is escalating due to the high infectivity. It is highly likely that dental professionals in upcoming days will come across COVID-19 patients and SARS-CoV-2 carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Caregivers also should take care of their children to avoid tooth trauma, if they play, protecting appliance should be used. When the restrictions were lifted, a series of non aerosol-producing procedures are recommended to minimize the risk of cross infection including chemomechanical caries removal, atraumatic restorative treatment, silver diamine fluoride, Hall Technique and so on [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers also should take care of their children to avoid tooth trauma, if they play, protecting appliance should be used. When the restrictions were lifted, a series of non aerosol-producing procedures are recommended to minimize the risk of cross infection including chemomechanical caries removal, atraumatic restorative treatment, silver diamine fluoride, Hall Technique and so on [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the exclusion of one duplicate article, the abstracts of the remaining 74 articles were screened, with 66 articles excluded for not meeting the inclusion criteria. Finally, eight articles were identified as eligible after full-text screening [2][3][4][5][6][7][8][9]. These eight articles are listed in Table 1, along with a summary of their key points.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, these resources have grown in all dental education areas, including resource administration, disaster response, and coordination at institutional and departmental levels to face such pandemic situations. A recent American study 7 (15) found that dental students are undergoing increased stress levels, and they felt that this COVID-19 outbreak affected their clinical learning. Recent insight from the United States of America, Brazil, and Australia (16) concluded that dental education and dental practices changed considerably because of the COVID-19 outbreak.…”
Section: Canceled Meetingsmentioning
confidence: 99%
“…Shah ( 6 ) from Pakistan opined that it is essential to implement specific protocols to minimize the transmission of COVID-19 infection to patients from other patients or medical tools and equipment. Kochhar et al ( 7 ) from north India recommended that a customized approach is necessary to safeguard children and their accompanying family members and health care professionals in the dental operatory from the novel Coronavirus. Bahramian et al ( 8 ) from Iran reported that social media's effect on updating knowledge on protocols and other necessary information on COVID-19 was beneficial for a worldwide approach to safety in the educational setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation